2011
DOI: 10.1590/s0100-67622011000700014
|View full text |Cite
|
Sign up to set email alerts
|

Estoque e crescimento em volume, biomassa, carbono e dióxido de carbono em Floresta Estacional Semidecidual

Abstract: RESUMO -O objetivo deste trabalho foi estimar o estoque e o crescimento em volume (V), biomassa (B), carbono (C) e dióxido de carbono (CO 2 ) em Floresta Estacional Semidecidual no Vale do Rio Doce, em Minas Gerais. Foram utilizados dados de inventários do estrato arbóreo (DAP > 5,0 cm), cujas parcelas permanentes foram medidas em 2002 e 2007, em estágios médio (Mata 1) e avançado (Mata 2) de regeneração da vegetação secundária. Com base no inventário de 2002, foram selecionadas espécies que apresentavam maior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…In a study by Figueiredo et al (2015), in a semideciduous seasonal forest, in the middle stage of regeneration, it was found an estimate of PAI in carbon of 0.994 MgC ha -1 year -1 , from 1994 to 2008, considering only the stem. Souza et al (2011) found an PAI in carbon of 0.14 MgC ha -1 year -1 for a semideciduous seasonal forest, also in the middle stage of regeneration, from 2002 to 2007, considering stems and branches. The PAI estimates found by these authors were much lower than those found in this study.…”
Section: Gementioning
confidence: 89%
“…In a study by Figueiredo et al (2015), in a semideciduous seasonal forest, in the middle stage of regeneration, it was found an estimate of PAI in carbon of 0.994 MgC ha -1 year -1 , from 1994 to 2008, considering only the stem. Souza et al (2011) found an PAI in carbon of 0.14 MgC ha -1 year -1 for a semideciduous seasonal forest, also in the middle stage of regeneration, from 2002 to 2007, considering stems and branches. The PAI estimates found by these authors were much lower than those found in this study.…”
Section: Gementioning
confidence: 89%
“…Esse fato amplia a ênfase nos últimos anos para o papel das florestas naturais na captura de CO2, corroborado pela avaliação do estoque de carbono em formações de Floresta Ombrófila Densa (CUNHA et al, 2009;SILVEIRA, 2010) e Mista (WEBER et al, 2005;AMARAL et al, 2010;WATZLAWICK et al, 2012;MOGNON et al, 2013;LIPINSKI et al, 2017;), Floresta Estacional Semidecidual (RIBEIRO et al, 2009;SOUZA et al, 2011;AMARO et al, 2013;DINIZ et al, 2015;) e biomas como Cerrado (MORAIS et al, 2013) e Caatinga (SANTOS et al, 2016).…”
Section: Introductionunclassified
“…In natural forest fragments, the differences observed between sites in wood, biomass, and carbon stocks in the tree component can be attributed to differences in floristic composition, diameter structure, and successional stage [25][26][27]37,57]. Moreover, the specific characteristics of each vegetation type can contribute to the different biomass stocks at each site, as the previous land use history of each site might also affect the biomass accumulation rates [27].…”
Section: Discussionmentioning
confidence: 99%